SIMULATION OF NITROGEN BALANCE UNDER SUB-SURFACE DRAINAGE CONDITIONS AT THEHRI MUKTSAR PUNJAB, USING THE DNDC MODEL V. 9.5 - MEHRAJ U DIN DAR; J. P. Singh; Kuldip Singh (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study: The aim of the study is DNDC model simulation for nitrogen balance in rice-wheat cropping system.